PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI PUSKESMAS TUNTUNGAN KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Tarigan, Dodi Evrata; Siagian, Nalom; Rajagukguk, Jonson; Panjaitan, Maringan; Tobing, Artha (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to analyze the effect of service quality on patient satisfaction of the Social Security Administering Agency (BPJS) Health at the Tuntungan Health Center, Pancur Batu District, Deli Serdang Regency. Service quality is one of the important factors in creating patient satisfaction, which in turn affects loyalty and the level of use of health services. The research method used is a survey with a quantitative approach, where data is collected through a questionnaire distributed to 100 respondents who are BPJS Health patients at the Health Center. Data analysis was carried out using a simple linear regression technique to test the relationship between service quality variables and patient satisfaction. The results of the study showed that there was a positive and significant effect between service quality and BPJS Health patient satisfaction at the Tuntungan Health Center. This indicates that the better the quality of service provided, the higher the level of patient satisfaction. This study provides recommendations for the Health Center to continue to improve the quality of service through training medical personnel and providing adequate facilities, in order to achieve higher patient satisfaction and increase the effectiveness of health services.